2011
DOI: 10.1111/j.1474-9726.2011.00738.x
|View full text |Cite
|
Sign up to set email alerts
|

The H3K27 demethylase UTX‐1 regulates C. elegans lifespan in a germline‐independent, insulin‐dependent manner

Abstract: Summary Aging is accompanied by alterations in epigenetic marks that control chromatin states, including histone acetylation and methylation. Enzymes that reversibly affect histone marks associated with active chromatin have recently been found to regulate aging in C. elegans. However, relatively little is known about the importance for aging of histone marks associated with repressed chromatin. Here we use a targeted RNAi screen in C. elegans to identify four histone demethylases that significantly regulate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
239
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(253 citation statements)
references
References 73 publications
12
239
0
2
Order By: Relevance
“…Given the exquisite responsiveness of chromatin modifiers to metabolic cues, the metabolic control of healthspan should reasonably involve a similar regulation of the epigenome (López‐Otín et al., 2016). Our current findings suggest that the healthspan‐promoting capacity of metformin might involve not only an indirect regulation of metabolo‐epigenetic fluxes, but also a direct targeting of key aging/senescence‐related chromatin regulators such as the H3K27me3 histone demethylase KDM6A/UTX (Jin et al., 2011; Maures, Greer, Hauswirth & Brunet, 2011; McCauley & Dang, 2014; Shah et al., 2013). A decrease in repression‐associated H3K27me3 (and an increased activity of the H3K27me3 demethylase KDM6A/UTX) is a key feature of the global chromatin reconfiguration occurring not only in somatic cells during the normal aging process but also in prematurely aging cells in HGPS and WS (Scaffidi & Misteli, 2005; Shah et al., 2013; Shumaker et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the exquisite responsiveness of chromatin modifiers to metabolic cues, the metabolic control of healthspan should reasonably involve a similar regulation of the epigenome (López‐Otín et al., 2016). Our current findings suggest that the healthspan‐promoting capacity of metformin might involve not only an indirect regulation of metabolo‐epigenetic fluxes, but also a direct targeting of key aging/senescence‐related chromatin regulators such as the H3K27me3 histone demethylase KDM6A/UTX (Jin et al., 2011; Maures, Greer, Hauswirth & Brunet, 2011; McCauley & Dang, 2014; Shah et al., 2013). A decrease in repression‐associated H3K27me3 (and an increased activity of the H3K27me3 demethylase KDM6A/UTX) is a key feature of the global chromatin reconfiguration occurring not only in somatic cells during the normal aging process but also in prematurely aging cells in HGPS and WS (Scaffidi & Misteli, 2005; Shah et al., 2013; Shumaker et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in repression‐associated H3K27me3 (and an increased activity of the H3K27me3 demethylase KDM6A/UTX) is a key feature of the global chromatin reconfiguration occurring not only in somatic cells during the normal aging process but also in prematurely aging cells in HGPS and WS (Scaffidi & Misteli, 2005; Shah et al., 2013; Shumaker et al., 2006). In addition, landmark observations in Caenorhabditis elegans have linked gain of H3K27me3 (and loss of the H3K27me3 demethylase UTX‐1) to extended longevity, strongly suggesting that preserving high levels of H3K27me3 by inhibiting KDM6/UTX may be critical for maintaining youthfulness (Jin et al., 2011; Maures et al., 2011; McCord et al., 2013; Shah et al., 2013). Despite conflicting data from different model systems, there is a trend for increases in activating histone marks (e.g., H3K4m2/3, H3K36me3) and decreases in repressive histone marks (e.g., H3K9m2/3, H3K27me3) indicative of a more actively transcribed genome, which is consistent with a well‐recognized open chromatin conformation in aging cells and organisms that culminates in the so‐called heterochromatin loss model of aging (Pal & Tyler, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The connection between heterochromatin maintenance and lifespan extension is further strengthened by studies in Caenorhabditis elegans and Drosophila (Rogina & Helfand, 2004; Hashimoto et al ., 2010; Jiang et al ., 2013; Whitaker et al ., 2013). Disruption of UTX‐1, a histone demethylase that reduces the heterochromatin epigenetic modification called histone H3 K27 trimethylation (H3K27me3), in C. elegans leads to increased H3K27me3 levels and prolonged lifespan (Jin et al ., 2011; Maures et al ., 2011). Moreover by modulating the expression of HP1, a protein required for the maintenance of heterochromatin, researchers have shown that increase or decrease HP1 levels leads to lifespan extension or shortening, respectively, in Drosophila (Larson et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Since mutations in some heterochromatin modifying enzymes have been shown to regulate the lifespan of C. elegans and Drosophila (Siebold et al ., 2010; Jin et al ., 2011; Maures et al ., 2011), it is possible that age‐associated changes of chromatin regulators could contribute to heterochromatin loss and TE activation. Nuclear lamins, the major structural components of the nuclear lamina that associate with the nuclear peripheral heterochromatin, are believed to contribute to the establishment and maintenance of the heterochromatin (Dechat et al ., 2008; Bank & Gruenbaum, 2011; Kim et al ., 2011; Meuleman et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…2011; Ni et al ., 2012), including the prolyl‐hydroxylase EGL‐9 (Lee et al ., 2010), which regulates the stability of hypoxia‐inducible factor‐1 (HIF‐1). HIF‐1 is a dimeric protein composed of α‐ and β‐subunits and in multiple species functions as a master transcription factor that coordinates survival during hypoxic conditions.…”
Section: Introductionmentioning
confidence: 99%